Tissue adhesion between distant plant species in parasitism and grafting. Issue 1 (1st January 2021) - Okayasu, Koji; Aoki, Koh; Kurotani, Ken-Ichi; Notaguchi, Michitaka
ABSTRACT: Plant grafting is generally performed between closely related species. Recently, we have discovered that Nicotiana species of Solanaceae show the ability to graft with distantly related plant species beyond the family. Graft adhesion with diverse angiosperms by Nicotiana species was probably facilitated by the secretion of a subclade of ß-1, 4-glucanases. The capability of interfamily grafting was also found in the model Orobanchaceae hemiparasitic plant, Phtheirospermum japonicum, which naturally invades to the tissues of host plants of different families. Transcriptome analysis indicated that the same clade of ß-1, 4-glucanase plays an important role in plant parasitism. Thus, the tissue adhesion between distant plant species occurs both naturally and artificially. Here, we further observed the capability of interfamily grafting in the stem holoparasitic genus, Cuscuta . These findings indicate that the natural process of tissue adhesion is a potential clue to improve plant-grafting techniques.